PENGARUH GREEN PRODUCT & PRAKTEK GREEN BUSINESS PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK DAUR ULANG PLASTIK DI JAKARTA, INDONESIA (JABODETABEK) - Soekrisman (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2020)
Based on the background of the problem of plastic waste, along with the advantages and disadvantages of various countermeasures that have been carried out by the private sector & the government. Therefore, this research was intentionally conducted to find out the extent of the effects of all efforts to overcome plastic waste in Indonesia. Research conducted is to determine the magnitude of the influence of green business practices and green products on the decision to purchase plastic recycling products in Jakarta, Indonesia (JABODETABEK). Furthermore, this study was conducted on 90 respondents who were considered to have the status of ever knowing, buying, or using local plastic recycling products (purposive sampling). This was done with a research design in the form of descriptive analysis and frequency. Continued with data collection techniques such as data observation, interviews, and questionnaires. Finally, the results of data calculations performed by the quantitative approach method and multiple linear regression analysis. After an analysis using the multiple regression research method, the results of the study show that both the independent variables of green products and green business practices have a significant influence on purchasing decisions.Keywords: green product, green business practices, purchasing decisions, plastic recycling products.